Educators in Qur’an (Education Spirituality Analysis in Surah Al-Kahfi Verses 60-82) - Ayu Era Wardhani; Dwi Ratnasari; Idrus Latif (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
To achieve educational goals in accordance with Islamic religious law, it is necessary to have a strong foundation, namely the Qur'an as a guide for Muslims. In the Qur'an, there are many commands of Allah SWT that are intended for His people to be carried out and prohibitions to be abandoned. Al-Qur'an Surah Al-Kahfi verses 60-82 describe the struggle of Prophet Musa to study with Prophet Khidir, it can be imitated by educators today in carrying out their profession as an educator. The method used in this writing is library research. The stages that the author did in this research were collecting research materials, reading library materials, making research notes, and processing the research notes. The importance of good interaction between educators and their students in order to achieve the desired educational goals, an educator is expected to have good character in accordance with the Uswah Hasanah owned by the Prophet Muhammad in order to achieve the desired goals. Good manners are expected to always be embedded in students when studying, an educator is expected to use the right method in educating, in order to create a good and efficient interaction process between the two.